2022
DOI: 10.53761/1.19.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Exploring academic procrastination: Perceptions, self-regulation, and consequences

Abstract: The current study examined how COVID-19 impacted urban college students’ engagement in their schoolwork and whether John Henryism mediated the relationship among demographic variables and engagement. Results demonstrated that John Henryism is a significant predictor of all three engagement outcomes (absorption, dedication, and vigor) and mediated the relationship between historically underrepresented students (Black and Latinx) and their vigor for engaging in schoolwork. Three themes emerged from the qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Again, we learned that identifying as a first-generation student (predominantly Black and Latinx) led to greater levels of John Henryism and subsequent aspects of the CVT process, i.e., value/ control and subsequent positive emotions. This confirmed the results of other studies (see Gaydosh et al, 2018;Brody et al, 2020;Torsney et al, 2022), demonstrating that John Henryism may be an important precursor to engagement and academic success for underrepresented students, especially minorities of color, who may have more competing goals (Neely et al, 2009), such as partor full-time job, than continuing generation White students. This study showed that a student's identity and high-effort coping (i.e., John Henryism) seamlessly integrated into the CVT/momentary engagement system.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Again, we learned that identifying as a first-generation student (predominantly Black and Latinx) led to greater levels of John Henryism and subsequent aspects of the CVT process, i.e., value/ control and subsequent positive emotions. This confirmed the results of other studies (see Gaydosh et al, 2018;Brody et al, 2020;Torsney et al, 2022), demonstrating that John Henryism may be an important precursor to engagement and academic success for underrepresented students, especially minorities of color, who may have more competing goals (Neely et al, 2009), such as partor full-time job, than continuing generation White students. This study showed that a student's identity and high-effort coping (i.e., John Henryism) seamlessly integrated into the CVT/momentary engagement system.…”
Section: Discussionsupporting
confidence: 87%
“…We posit that John Henryism, as a coping strategy in a learning environment in which race and ethnicity influence context and vice-versa, activates control and value. Specifically, we are using James (1994James ( , 2019 hypothesis that John Henryism is a critical precursor to engagement and subsequent action for underrepresented minorities in contexts where they may perceive environmental stress (Torsney et al, 2022). Therefore, we believe that as control and value are activated by John Henryism, increases in positive activating emotions (e.g., excitement or activity) and decreases in negative activating emotions (e.g., irritation or anxiety) can be expected.…”
Section: Precursors To Engagement: Integrating John Henryism Into Cvtmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have discussed, in the interim John Henryism is not entirely maladaptive. For example, Torsney et al (2022) demonstrated that higher levels of John Henryism-especially for historically underrepresented racially minoritized students-are adaptive when it comes to engagement in schoolwork during the COVID-19 pandemic. In other words, John Henryism was a protective factor for keeping some of the most vulnerable students engaged in their schoolwork during an incredibly challenging time.…”
Section: John Henryism and College Studentsmentioning
confidence: 99%